Atividade antiproliferativa das folhas de Arctium lappa L. - Machado, Fabio Bahls (2010)
Arctium lappa L. the Asteraceae family is a plant introduced from Japan and cultivated in Brazil, and is used in folk medicine around the world in "curing" various diseases. Studies show that the parties studied are the roots and fruits, since they show various biological activities among them anticancer, antioxidant, antiviral, hepatoprotective capacity, among others. But studies of their leaves are scarce. This study aims to collect and identify plant species, as well as evaluation of in vitro antiproliferative crude (CE) and semipurified extracts, and isolated compounds in Caco-2 cells. The plant species was confirmed by comparison with the nomenclatural type as Arctium lappa L. From the dry and comminuted leaves A. lappa, produced to the CE solution with 50% hydro, for turboextraction for 15 min. The test in Caco-2 cells showed activity of CC50 347.6 mg/mL. Then the CE was partitioned with hexane, ethyl acetate and n-butanol. The ethyl acetate fraction (EAF) showed antiproliferative activity of CC50 24.7 g/mL. The EAF was submitted to vacuum liquid chromatography (VLC) containing silicagel, using various solvent systems of increasing polarity, and the ethyl acetate subfraction (EAFS) showed the best result with CC50 21.9 g/mL against the Caco-2. The subfraction EAFS was further chromatographed by chromatography "flash" silicagel, and the compounds isolated was onopordopicrin (1), dehidromelitensin-8- (4'-hidroxy-metacrylate) (2), dehidromelitensin (3), melitensin (4) , dehidrovomifoliol (5) and loliolide (6) weve isolated. The compounds 2, 3, 4 and 5 were first identified in the species. The compound onopordopicrin showed a CC50 of 19.7 g/mL, demonstrating to be a possible drug of choice for further studies in other cell lines.